Perceived Psychological Well-Being of Lithuanian Judges - Valickas, Gintautas; Vanagaitė, Kristina (Teisė, 2024)
The article examines the psychological well-being of judges. The aim of the study is to reveal the peculiarities of Lithuanian judges’ psychological well-being. The following questions were sought to be answered: (1) what is the character of perceived psychological well-being of judges; (2) does there exist any relation among the psychological well-being of judges, experience accumulated by the participants, and their sociodemographic characteristics. The participants (307 judges from various Lithuanian courts) completed the Psychological Well-Being of Judges questionnaire developed by the authors of this paper. The findings revealed that the psychological well-being of judges perceived by the participants was more positive than negative: from thirteen components of psychological well-being, six components elicit a strong satisfaction, two – moderate and five – weak satisfaction of judges. The judges’ experience of psychological well-being was related with the gender, age, work experience, work place (District Court, County Court, or The Supreme Court of Lithuania, The Supreme Administrative Court of Lithuania, and The Court of Appeal of Lithuania) and size of the city or town they were working in: a metropolitan city (Kaunas, Klaipėda, Panevėžys, Šiauliai, Vilnius) or other towns of Lithuania. The data gathered suggest that psychological well-being is a fairly relevant problem for Lithuanian judges; therefore, the Judicial Council, leaders of the Courts, and the National Courts Administration should devote more attention to it.
Keywords: psychological well-being of judges; components of the psychological well-being; satisfaction of judges with the experienced psychological well-being; relations between the psychological well-being and socio-demographic characteristics